Identification and Transcriptional Modulation of the Largemouth Bass, Micropterus salmoides, Vitellogenin Receptor During Oocyte Development by Insulin and Sex Steroids - Dominguez, Gustavo A. (Society for the Study of Reproduction, Inc., 2012)
Fish vitellogenin synthesized and released from the liver of oviparous animals is taken up into oocytes by the vitellogenin receptor. This is an essential process in providing nutrient yolk to developing embryos to ensure successful reproduction. Here we disclose the full length vtgr cDNA sequence for largemouth bass (LMB) that reveals greater than 90% sequence homology with other fish vtgr sequences. We classify LMB Vtgr as a member of the low density lipoprotein receptor superfamily based on conserved domains and categorize as the short variant that is devoid of the O-glycan segment. Phylogenetic analysis places LMB Vtgr sequence into a well-supported monophyletic group of fish Vtgr. Real-time PCR showed that the greatest levels of LMB vtgr mRNA expression occurred in previtellogenic ovarian tissues. In addition, we reveal the effects of insulin, 17beta-estradiol (E(2)), and 11-ketotestosterone (11-KT) in modulation of vtgr, esr, and ar mRNAs in previtellogenic oocytes. Insulin increased vtgr expression levels in follicles ex vivo while exposure to E(2) or 11-KT did not result in modulation of expression. However, both steroids were able to repress insulin-induced vtgr transcript levels. Coexposure with insulin and E(2) or of insulin and 11-KT increased ovarian esr2b and ar mRNA levels, respectively, which suggest a role for these nuclear receptors in insulin-mediated signaling pathways. These data provide the first evidence for the ordered stage-specific expression of LMB vtgr during the normal reproductive process and the hormonal influence of insulin and sex steroids on controlling vtgr transcript levels in ovarian tissues.